Customer Engagement, Customer Equity & Intention to Reuse Mobile Service Applications (A Case Study of Dana Application Users) - Agung Prastio, Asep; Ridanasti, Erlita (International Journal of Management Science and Information Technology, 2023)
This study aims to examine the effect of Customer engagement on Customer Equity (Value Equity, Relationship Equity, and Brand Equity) and Repurchase Intention on Mobile service applications. The population used in this study are Indonesian students who have made transactions/purchases through the Dana application. The number of samples used in this study was 200 respondents. Research data was collected by distributing questionnaires through an Online Survey system using Google Forms. The analysis technique used in this study is the PLS-SEM (Partial Least Square - Structural Equation Model) analysis technique with the SmartPLS program to test the hypothesis. The results showed that customer engagement positively affects value equity, relationship equity, and brand equity, which in turn can positively affect repurchase intentions.